Gambaran Penggunaan Pil KB Tentang Ketepatan Cara Minum di PMB Desa Pagendingan Kec. Galis Kabupaten Pamekasan - Tety Ripursari; Emi Yunita (Universitas Islam Madura, 2022)
Contraceptives are methods used to control pregnancy. Based on the profile data of the Surabaya City Health Office in 2016, the highest family planning (Family Planning) pill acceptors were located in Tambaksari District, amounting to 4440 acceptors. According to WHO data, the failure rate for birth control pills reaches 90 per 1000 people. This can happen due to a lack of knowledge and information related to things that can reduce the effectiveness of the birth control pill.[1] Based on a preliminary study in Pagendinggan Village, Kec. Galis Pamekasan Regency obtained as many as (53.34%) the wrong way of drinking, namely when experiencing forgetting to drink or during menstruation. The purpose of this study was to determine the use of birth control pills in PMB Hj. Yuni Sri Rahayu, SST Kec. Galis Pamekasan Regency. This type of research is descriptive. With a cross sectional approach. The independent variable in this study was the use of birth control pills.[2] The sample in this study amounted to 30 acceptors at PMB Hj. Yuni Sri Rahayu, SST Kec. Galis Pamekasan Regency was taken by total sampling technique. Data collection techniques using questionnaires. The results of this study indicate that from the level of education most of the acceptors have a basic education level, namely 17 respondents (56.67%) about knowledge of how to take birth control pills. Based on these conclusions, the solution that can be done is to provide counseling to the parties concerned, namely the acceptors themselves, husbands, and families because counseling can provide knowledge to acceptors about birth control pills such as side effects, when to use and how to take birth control pills correctly, loss. and health workers can improve the quality of counseling by collaborating with family planning counseling and related agencies, so that acceptors can easily understand the counseling provided so that acceptors or the public are not wrong in using contraceptives. Keywords: use of birth control pills